1958
DOI: 10.1037/h0043950
|View full text |Cite
|
Sign up to set email alerts
|

Predicting school achievement for bilingual pupils.

Abstract: Teachers, and other school i>ert>oniicl of the Territory of Guam have long been aware of the need for adequate predictors of school achievement for their bilingual pupils. In December of 1956, Guam's Department of Education authorized a study to discover to what extent, if any, currently available tests would provide such predictions. Guam is a territory whose cultural patterns are rapidly changing. From a Spanish type of church-dominated society, from a military paternalism, Guam is becoming infused with curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1962
1962
2000
2000

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The rank-order correlation of the two tests is .42 which is significant at the .05 level. Cooper (1958) published a correlation of .62 for these two tests with a sample of fifth graders.…”
Section: Resultsmentioning
confidence: 99%
“…The rank-order correlation of the two tests is .42 which is significant at the .05 level. Cooper (1958) published a correlation of .62 for these two tests with a sample of fifth graders.…”
Section: Resultsmentioning
confidence: 99%
“…This paper proposes the creation of a fieldbased project consisting of two or three experimental and two or three control schools for the development of the design. In the late fifties and early sixties, immediately prior to the rebirth of U.S. bilingual education C. A1?-dersson' and Boyer, 1970), psychological and educational researchers had show substantial interest in U.S. bilingual students and on the effects of bilingualism on the individual (Bovet, 1963;Cooper, 1958;Darcy, 1963;Diebold, 1961;ErvinTripp, 1961;Jensen, 1962;Lado, Lambert and Andersson, 1962;Lambert, 1966;Lambert, Ha-.velka and Crosby, 1958;Lambert, Havelka and Gardner, 1959;Love, 1962;Mackey, 1962;Morrison, 1958;Peal and Lambert, 1962;Pike, 1969). The federal government has set the pace for growth and has determined the character of bi lingual education in the nation, and yet, the Bi lingual Education Act of 1968 did not even provide a definition of bilingual education (U.S. Com mission on Civil Rights, 1975).…”
Section: Rationale For a Field-based Research And Development Projectmentioning
confidence: 97%
“…It is composed of a number of items which require no reading nor attention to instructions written on the test forms. Several studies (Cooper, 1958;Richie, 1954;Rosenblum, 1955) have questioned the cultural bias of the test and some of the initial claims for socio-economic fairness are no longer made. The test may have value for use with poor readers (Justman, 1955), but Smith (1956) has indicated that auding ability (ability to understand spoken language) is a major source of bias in the test.…”
Section: Davis Eells Games (Lqiis) World Book Companymentioning
confidence: 99%